Instructional Supervision for Culturally Responsive Teaching - Stephen P Gordon; Sara Espinoza (Educational Considerations, 2020)
Instructional Supervision for Culturally Responsive Teaching Stephen P. Gordon Professor Emeritus, Texas State University, sg07@txstate.edu Sara Espinoza School Designer, Teaching for Transformation, sara.espinoza@cace.org Abstract In this position paper we argue that clinical supervision and other processes of instructional supervision, if focused on collaborative inquiry rather than external critique, can assist teachers to engage in more culturally responsive teaching (CRT). The article begins with a brief review of CRT, including its definition, principles, and goals. We then describe how clinical supervision based on a collaboration, mutual trust, and collegiality can assist a teacher to reflect on classroom behaviors, engage in self-critique, and adopt new teaching behaviors. Following the discussion of clinical supervision, we illustrate how other supervision processes—professional development, professional learning communities (PLCs), curriculum development, and action research—can be combined with clinical supervision to support CRT. Professional development can help teachers to develop a variety of capacities associated with CRT. In PLCs, teachers can assist each other to reflect on classroom experiences, plan for needed change, and assist each other to implement and assess that change. With the assistance of the supervisor, teachers can work together to design and implement culturally responsive curriculum. The supervisor and teachers can engage in action research for CRT in which they select a focus area, design an action plan, implement the plan, and assess results. The article concludes with a case study that illustrates how all five of the supervision processes discussed can be integrated in a comprehensive effort to promote CRT.
Keywords: culturally responsive teaching; instructional supervision; clinical supervision; professional development